The influence of product quality and service quality on consumer satisfaction - Ahyani, Ahyani (Journal of Economics and Business Letters, 2023)
This study aims to determine the effect of product and service quality on customer satisfaction at Andaf Corp Digital Printing in Bekasi. The research methodology used is the Associative method. The population in this study were all consumers who purchased at Andaf Corp Digital Printing in 2021. As many as 1,990 people using the Slovin Formula, a sample of 95 respondents was obtained. Methods of data analysis using simple linear regression test the results showed that There is an effect of product quality on consumer satisfaction at Andaf Corp Digital Printing in Bekasi. There is an effect of service quality on customer satisfaction at Andaf Corp Digital Printing in Bekasi. There is an effect of product quality and service quality on customer satisfaction at Andaf Corp Digital Printing in Bekasi. The correlation value is 0.892. The value of the coefficient of determination is 79.6%.